La représentation de l’intérêt collectif environnemental devant le juge civil : après l’affaire Erika et avant l’introduction dans le Code civil du dommage causé à l’environnement - Marie-Pierre Camproux Duffrene (VertigO)
This study envisages the possibility to consider the environment not as a personal or general interest but as a collective one. This concept little used or even glossed over is thus analyzed in French law and in the environmental context to characterize this environmental collective interest. The analysis is then used to reveal the specificity but also the coherence of the civil action in terms of admissibility and validity in case of environmental damage. Indeed, the environmental collective interest makes the distinction between group action (defending the addition of individual interests) and action in defense of indivisible collective interests easier. It also provides useful precisions on the ecological damage still blurred (collective damage) and the terms of its compensation in kind (rehabilitation or natural equivalent) if possible.